Understanding Multilingualism for Promoting Indian Languages, Arts and Culture in Teacher Preparation: NEP 2020. - Islam, Quazi Ferdoushi; Hasan, Muzammil (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2026)
Realizing the potential of India as a language rich nation, the National Education Policy (NEP), 2020 has significantly used this language diversity as an ace. The Constitution of India guarantees minorities, whether based on religion or language, the right to establish and administer educational institutions of their choice (Article 30). Similarly, Article 29, of the Constitution of India states the protection of interests of minorities and that any section of citizens residing in the territory of India having a distinct language, script and culture shall have the right to conserve the same. Therefore, our educational institutions, especially teachers are the best means to create an inclusive, multi-cultural society as they are centrally placed to prepare students with constitutional values as global citizens. NEP, 2020 aims at just that: preparing our young minds to be global citizens yet strive at the core of Indianness. Hence, teacher preparation must take into account the needs of all learners and the aspirations of their families. This paper attempts to throw light on understanding multilingualism for promoting Indian languages, arts and culture against the backdrop of the National Education Policy, 2020 and teacher preparation. It also discusses the crucial significance of culture on language learning. Language is not just a means of expression. It is much deeper. It is an expression of one’s cultural identity. Language learning in a child is crucial. It supports the ability of a child to communicate and express and understand feelings.